Razvoj očesa - Štiblar-Martinčič, Draga (Medicinski razgledi, 2004)
The eye and, the sensory organ for vision, develops from the sensory placodes in the ectodermal germ layer like the other sense organs, in response to induction from the central nervous system. A single eye field separates into two optic primordia after sonic hedgehog stimulus expressed in the prechordal plate. Eye development is first evident at the beginning of the fourth week. The basic structures for eye development are the neuroeaodermal optic vesicle,which is a lateral evagination from the wall of the diencephalon, neural crest ectomesenchyme and the overlying surface eaoderm. Further development is coordinated by successive signals and interacting intluences ofthe above-mentioned tissues. The optic vesicle contacts the surface ectodexmand triggers a response that leads to thickening of the eaoderm, the so-called lens placode, which later develops into a mature lens. While the lens placode internalizes to form the lens vesicle, the distal optic vesicle invaginates to form the optic cup. The inner layer of the optic cup develops into the neuroretina, while the outer layer forms the rerinal pigmented epithelium. The proximal region of the optic vesicle is the optic stalk that connects the optic vesicle with the rostral part of the diencephalon. Prom theoptic stalk, the optic nerve develops. Thmugh the optic fissure, the hyaloid artery enters the eye and its proximal part is left as the central retinal artery. Successive signals between the optic vesicle, surrounding mesenchyme in the ectoderm around the lens placode induce the development of auxiliary eye structures. The genes which are crucial for eye development are Pax2 and Pax6.
Keywords: Eye; Leča očesna; Mrežnica; Embryology; Cornea; Oko; Conjunctiva; Roženica; Veznica; Retina; Lens, Crystalline; Oko, anomalije; Solzila; Uvea; Veke; Iris; Optic Nerve; Vidni živec; Šarenica; Eyelids; Lacrimal Apparatus; Žilnica; Eye Abnormalities; embriologija